2013
DOI: 10.1149/05005.0279ecst
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Level Transient Spectroscopy of MOS Capacitors on GeSn Epitaxial Layers

Abstract: Deep levels present in MOS capacitors, fabricated on GeSn epitaxial layers on Ge-on-Si substrates have been studied by Deep-Level Transient Spectroscopy (DLTS). The gate dielectric is composed of 9 nm Al2O3 deposited by Molecular Beam Epitaxy (MBE) on two different types of Interfacial Oxide Layers (IOL). It is shown that the density of interface traps (Dit) near the valence band edge is significantly reduced for GeSn epilayers compared with the same gate stack on a Ge cap. At the same time, several deep-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…106 In the case of relaxed Ge virtual substrates, DLTS revealed the presence of a band of hole traps close to mid gap in p-type layers, with a peak maximum at about E V +0.28 eV. 105,107 Other studies reported shallower hole traps and a near mid-gap electron trap. 108 It has also been shown that the presence of TDs in SRBs accelerates the diffusion of n-type dopants (e.g., P) and, therefore, affects the (shallow) junction formation.…”
Section: Strained Si Layers On a Strain Relaxed Sige Buffer Layer-str...mentioning
confidence: 96%
“…106 In the case of relaxed Ge virtual substrates, DLTS revealed the presence of a band of hole traps close to mid gap in p-type layers, with a peak maximum at about E V +0.28 eV. 105,107 Other studies reported shallower hole traps and a near mid-gap electron trap. 108 It has also been shown that the presence of TDs in SRBs accelerates the diffusion of n-type dopants (e.g., P) and, therefore, affects the (shallow) junction formation.…”
Section: Strained Si Layers On a Strain Relaxed Sige Buffer Layer-str...mentioning
confidence: 96%
“…Transmission Electron Microscopy (TEM) analysis of the structures has shown pin holes in the Al 2 O 3 oxide layers. Consequently in figure 1b, we observe a high depletion current, indicating that the devices are quite leaky, for the relatively large area under investigation (21). The pin holes as well facilitates minority electron injection from the gate during forward bias for carrier recombination.…”
Section: Resultsmentioning
confidence: 90%
“…For that purpose MOS capacitors with a 9nm Al 2 O 3 gate dielectric on top of a GeO 2 interface layer have been fabricated. Initial DLTS results have been reported previously (21). Here a more detailed study of the deep levels is undertaken to identify their origin.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In order to have a more detailed understanding of origin of the electrical activity of TDs in (Si)Ge hetero-epitaxial layers, more fundamental analysis methods can be applied to p-n junctions, like Deep Level Transient Spectroscopy (DLTS) [20]. In the case of relaxed Ge virtual substrates, DLTS has revealed the presence of a band of hole traps close to mid gap in p-type layers, with a peak maximum at about E V +0.28 eV [19,21]. Other studies reported shallower hole traps and a near mid-gap electron trap [22].…”
Section: The Electrical Activity Of Threading Dislocations In Group I...mentioning
confidence: 99%